Ehlers-Danlos Syndrome - living with chronic pain. Current knowledge of the disease - Olszak, Joanna; Kapłan, Wojciech; Rachwał, Dominika; Piątek, Ewa; Zalewa, Karolina; Bartoszek, Lidia; Czelej, Magdalena; Stachowicz, Hubert; Mazurek, Joanna (Journal of Education, Health and Sport, 2023)
Ehlers Danlos Syndrome (EDS) is a group of the most common inherited connective tissue disorders. The main symptoms of this syndrome are excessive skin flexibility, joint hypermobility and blood vessels fragility. The diagnosis is based on clinical symptoms, but to confirm the type of EDS, it is necessary to identify the collagen-encoding gene or protein interacting with it. The group of Ehlers and Danlos diseases include fourteen types, the most common are classic, vascular, hypermobile, arthrochalasis, kyphoscoliotic and dermatosparaxis. [15] Connective tissue plays a key role in the process of movement, constituting the main component of bones, joint cartilage, tendons, ligaments and intervertebral discs. In addition, connective tissue is a part of every internal organ including the intestines and parenchymal organs and the cardiovascular system.[19] For this reason, patients with EDS show symptoms of many diseases, including respiratory, muscular, skeletal and vascular. Women suffering from EDS often struggle with complications during their pregnancies. Psychological and emotional issues are also common.[6] However, the most noticeable and debilitating symptom of EDS is pain, which is often severe and chronic. The pain occurs in approximately 90% or more of EDS patients.[8] Successful pain management in patients with EDS is a major challenge for specialists. The treatment involves non-steroidal anti-inflammatory drugs, acetaminophen, opioids and physiotherapy. Also marijuana, traditional chinese treatments, herbal remedies are considered to reduce the severity of the symptoms. [9] During the creation of this article, the authors analyzed the clinically relevant knowledge of EDS treatment and management based on research published on Pubmed.